45. CURRENT STATUS OF NUTRITIONAL CARE FOR PATIENTS AND RELATED FACTORS AT NATIONAL LUNG HOSPITAL IN 2019 (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe knowledge, attitudes and practices in nutritional care for patients of nurses and related factors at National Lung Hospital in 2019.Methods: The cross - sectional study, through direct interviews with 213 nurses in 13 clinical departments.Results: 57.7% of nurses have good knowledge, 78.4% of nurses have positive attitude and 62.9% of nurses have good practice in nutritional care for patients. There is a statistically significant relationship between educational level, training, supervision, knowledge, attitude and help of colleagues with nutritional care practice of nurses (p
Keywords: Nurses, nutritional care, National Lung Hospital.